Винодельческая отрасль Украины на рынках Европы - Криворотько, И.А.; Мамутова, З.М. (Культура народов Причерноморья, 2014)
Статья Винодельческая отрасль Украины на рынках Европы содержит анализ
современного состояния винодельческой отрасли Украины, в том числе факторов, сдерживающих ее
развитие, и предпосылок для будущего роста. Дана оценка потенциальных перспектив развития
отрасли в контексте роста экспорта и занятия определенной ниши на рынке Европы. Разработаны
рекомендации по повышению конкурентоспособности на Европейском рынке украинской продукции
винодельческой отрасли. Стаття Виноробна галузь України на ринках Європи містить аналіз сучасного стану
виноробної галузі України, в тому числі факторів, що стримують її розвиток, і передумов для
майбутнього зростання. Дана оцінка потенційних перспектив розвитку галузі в контексті зростання
експорту і заняття певної ніші на ринку Європи. Розроблено рекомендації щодо підвищення
конкурентоспроможності на Європейському ринку української продукції виноробної галузі. Article Wine industry of Ukraine in the markets of Europe contains analysis of modern trends of wine
industry within Ukraine, including factors blocking its development and factors for the future growth. Potential
perspectives of future growth have been considered and evaluated thoroughly. The article represents main
features of wine industry in Ukraine and other countries of Europe, peculiarities of its technology, legal
difficulties, tax policy, state support and investments experience in this field.
The peculiar interest has been paid to the characters that differ Ukrainian industry from European one.
Statistical information has been used in order to demonstrate the main differences and predict future way of
development.
Recommendations on future steps for government as well as business entities have been developed: marketing
activity, legal improvements, innovative initiatives, external markets investigation, state strategy realization,
state programs of industry support implementation, production quality increase by means of certification
procedures, their monitoring and control.